Analysis of Various Physical and Chemical Parameters of River Jehlum in Srinagar City (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water tests were gathered from stream  Jhelum at various areas over a stretch of 20 km from  Lasjan to Parimpora in the Srinagar city of Jammu &  Kashmir (UT), India. These examples were dissected for  14 water quality factors - physical and chemical  boundaries. The information related physico-chemical  boundaries of water of waterway Jehlum acquired during  the review have been referenced underneath in Table 1.  During the course of study, it was additionally seen that  the convergence of a portion of these boundaries was not  in agreement to as far as possible suggested by World  Health Organization. This could have a unmistakable  effect on life. The outcomes acquired during the review  show that the topographical area and season  straightforwardly affect the different physico-substance  boundaries of stream Jehlum. It is accepted that this study  will be useful in figuring out control technique in not so  distant future.
Keywords: Chemical analysis; Metal content; River Jhelum; Monitoring; Contamination